Really learn 100 more phrasal verbs (Oxford University Press, 2007)
Volume 2 of the successful teach-yourself workbook on phrasal verbs. Using the same tried and tested format, this book teaches learners a further 100 essential phrasal verbs used in everyday English and gives them opportunities to practise using them in a variety of exercises. Both books together will give a sound knowledge of this tricky area of English.